Donor-derived Ehrlichiosis: 2 Clusters Following Solid Organ Transplantation. (30th July 2021) - Saha, Aditi; Browning, Charles; Dandamudi, Raja; Barton, Kevin; Graepel, Kevin; Cullity, Madeline; Abusalah, Wala; Christine, Du; Rossi, Carla; Drexler, Naomi; Basavaraju, Sridhar V; Annambhotia, Pallavi; et al.
Abstract: Ehrlichiosis has been infrequently described as transmissible through organ transplantation. Two donor-derived clusters of ehrlichiosis are described here. During the summer of 2020, 2 cases of ehrlichiosis were reported to the Organ Procurement and Transplantation Network (OPTN) and the Centers for Disease Control and Prevention (CDC) for investigation. Additional transplant centers were contacted to investigate similar illness in other recipients and samples were sent to the CDC. Two kidney recipients from a common donor developed fatal ehrlichiosis-induced hemophagocytic lymphocytic histiocytosis. Two kidney recipients and a liver recipient from another common donor developed ehrlichiosis. All 3 were successfully treated. Clinicians should consider donor-derived ehrlichiosis when evaluating recipients with fever early after transplantation after more common causes are ruled out, especially if the donor has epidemiological risk factors for infection. Suspected cases should be reported to the organ procurement organization and the OPTN for further investigation by public health authorities. Abstract : Ehrlichiosis is a rare donor-derived infection. Simultaneous manifestation as fatal hemophagocytic lymphocytic histiocytosis in organ transplant recipients has not been reported. Early detection and empiric ehrlichiosis treatment may improve outcomes.